Osteogenic and Chondrogenic Potential of the Supramolecular Aggregate T-LysYal® - Di Benedetto, Adriana; Posa, Francesca; Marazzi, Mario; Kalemaj, Zamira; Grassi, Roberta; Lo Muzio, Lorenzo; Comite, Mariasevera Di; Cavalcanti-Adam, Elisabetta Ada; Grassi, Felice Roberto; Mori, Giorgio (Frontiers in Endocrinology, 2020)
Hard tissue regeneration represents a challenge for the Regenerative Medicine and Mesenchymal stem cells (MSCs) could be a successful therapeutic strategy. T-LysYal® (T-Lys), a new derivative of Hyaluronic Acid (HA) possessing a superior stability, has already been proved efficient in repairing corneal epithelial cells damaged by dry conditions in vitro. We investigated the regenerative potential of T-Lys in the hard tissues bone and cartilage. We have previously demonstrated that cells isolated from the tooth germ, Dental Bud Stem Cells (DBSCs), differentiate into osteoblast-like cells, representing a promising source of MSCs for bone regeneration. Herewith, we show that T-Lys treatment stimulates the expression of typical osteoblastic markers, such as Alkaline Phosphatase (ALP) and Osteopontin (OPN), determining a higher production of mineralized matrix nodules. In addition, we found that T-Lys treatment positively affects αVβ3 integrin expression, key integrin in the osteoblastic commitment, leading to the formation of focal adhesions (FAs). The efficacy of T-Lys was also tested on chondrogenic differentiation starting from human articular chondrocytes (HACs) resulting in an increase of differentiation markers and cell number.